Bridging Worlds: enhancing English Teaching through a culture-based approach in Iranian Kurdistan - Jamal Barkhoda; Abdullah Azizi; Barham Sattar Abdulrahman (Cogent Education)
This study explores the culture-based teaching (CBT) narratives and experiences of English language teachers in the Hawraman Region, aiming to understand their perceptions and experiences through an interpretative and qualitative research approach using a Narrative Inquiry strategy. Specifically, twenty experienced teachers (14 males and 6 females) were selected via purposive sampling, and data were collected through episode interviews and analyzed using Braun and Clarke (2006) thematic analysis. The findings revealed that CBT encompasses four meta-narratives: context-based, interaction-based, adaptive-based, and value-based. Furthermore, essential skills for implementing CBT include multicultural literacy, cultural experience, and cultural competence. Additionally, the study highlighted challenges at the local level, such as cultural duality and cultural self-alienation, and critiqued the centralized and authoritarian nature of the Iranian educational system, which prioritizes monolingualism and Persian language hegemony. Consequently, the findings suggest that CBT can enhance teachers’ commitment to and appreciation of students’ cultures and lifestyles, leading to improved performance in teaching English—a significant challenge within Iran’s educational system. Ultimately, this study offers a detailed examination of the culture-based approach to language teaching in Iran, underscoring the need to consider students’ cultural backgrounds within diverse educational contexts.